Ketahanan Galur-Galur Padi Pup1 terhadap Penyakit Blas - Tasliah, Tasliah; Prasetiyono, Joko; Suhartini, Tintin; Soemantri, Ida Hanarida (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Blast is one of major disease on the upland rice in Indonesia. Upland rice lines derived from Kasalath and NILC443 crosses, containing Pup1 gen locus had been developed and evaluated for P fertilizer efficiency. Those lines would be evaluated for blast resistance, due to the fact that Pup1 locus contains genes involved in plant defend mechanism to disease, including blast disease. The BC2F5 plants derived from six crosses (DK, DN, SK, SN, BK, BN) were used in this research. Responses to blast disease in the green house were evaluated at ICABIOGRAD Bogor from March to April 2011, using combination of three blast races (race 173, 033, and 133). The response to blast disease in the field was evaluated at Taman Bogo Research Station, Lampung, and at farmerâs field in Cikeusal Village, Banten, from January to April 2011. Molecular analysis to trace Pup1 gene locus was conducted at the Molecular Biology Laboratory, using specific primer K20-2, from January to August 2013. Based on the molecular analysis all Pup1 lines showed homozygoes alleles, except the heterozygoes alleles on SK7, SK8, SK15, SK16, BN8 line, which were then not included in the next planting. The responses to blast at greenhouse among lines varied, but the Pup1 lines were mostly at level of moderate resistan (AT). Based on the result from the field experiment, most of Pup1 lines were resistance, however the susceptible check plant (Kencana Bali) did not show blast fungus infection. Differences of the result might be due to the blast testing at the green house which was more favorable for blast fungal growth. The effect of Pup1 gene locus showed clearly on resistance of plants obtained from Situ Bagendit cross, where Situ Bagendit was susceptible and does not contain the Pup1 locus. Additional of Pup1 locus in Situ Bagendit genome had increased the degree of resistant to blast.